Teacher perceptions of student speech A quantitative study - Oliver, Rhonda; Haig, Yvonne (John Benjamins Publishing Company, 2005)
This study reports on teachers’ attitudes towards their students’ speech varieties of English. A sample of 172 primary, district high and secondary teachers in Western Australian schools was surveyed on their attitudes towards language variation and towards their students’ use of specific English variants. The teachers were found to have generally conservative attitudes, particularly with regard to their students’ use of non-standard features. These features were also associated with falling language standards. The impact of the teacher background factors of gender, age, level of teaching qualification, teaching experience and professional development on attitudes was also considered. However, only teacher qualifications and length of experience were found to be significant and this influence was restricted to attitudes towards language varieties. Such findings have important implications for speakers of non-standard sociolects who would tend to use these features more often. It is of particular concern where teachers associate the use of non-standard varieties with lower academic ability as has been found in other research. The findings suggest that teachers need to understand the relationships between standard and non-standard varieties, written and spoken forms, formal and informal registers, and developmental and non-standard features.